Spatial Perception and Humanistic Innovation in Smart Cities: A Systematic Review - Wang, Tongwen; Zhou, Wuzhong (Distributed, Ambient and Pervasive Interactions, 2019)
The literature on spatial perception from the context of China and abroad generally presents situation in which the research perspective is rich, and the research methods are diverse. From the research content of the literature, almost all of them cover the objective existence of space and the subjective perception of people. This paper uses the literature review method to analyze and summarize 50 documents in the world which it draws conclusions related to spatial perception. This paper explores the relevant elements of spatial perception in the traditional sense from the microscopic and macroscopic perspectives. At the level of reflection, under the scope of smart city construction, we will explore more on the interactive spatial perception for the future because of the additional technology. This paper is based on the existing literature on how to integrate spatial perception with humanistic innovation in smart cities.